2019
DOI: 10.1002/anie.201901783
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of C(aryl)−CH3 Bonds in the Absence of Directing Groups under Transition Metal Free Conditions

Abstract: Organic chemists now can construct carbon–carbon σ‐bonds selectively and sequentially, whereas methods for the selective cleavage of carbon–carbon σ‐bonds, especially for unreactive hydrocarbons, remain limited. Activation by ring strain, directing groups, or in the presence of a carbonyl or a cyano group is usually required. In this work, by using a sequential strategy site‐selective cleavage and borylation of C(aryl)−CH3 bonds has been developed under directing group free and transition metal free conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 51 publications
1
23
0
1
Order By: Relevance
“…The reaction proceeds via the addition of TBN to CCb ond followed by a sequence of hydration,i somerization and aromatic C(sp 2 )ÀH oxidation (Scheme 44). [70] In this product water is the origin of two oxygen atoms which was confirmed by 18…”
Section: Scheme31 Transamidation Of Secondaryamidesmentioning
confidence: 65%
See 2 more Smart Citations
“…The reaction proceeds via the addition of TBN to CCb ond followed by a sequence of hydration,i somerization and aromatic C(sp 2 )ÀH oxidation (Scheme 44). [70] In this product water is the origin of two oxygen atoms which was confirmed by 18…”
Section: Scheme31 Transamidation Of Secondaryamidesmentioning
confidence: 65%
“…Diborylation product can be obtained by the sequential run of standard condition albeit in a low yield of 31 %. Based on the preliminary mechanistic study it was confirmed that the reaction continues via a sequential radical demethylative C−C bond cleavage followed by borylation (Scheme ) …”
Section: Outlines Of the Reactions Involving Tbnmentioning
confidence: 99%
See 1 more Smart Citation
“…2019 年, 康彦彪课题组报道了加热条件下促进的 芳基羧酸 NHPI 酯的脱羧硼酯化反应(图 10) [30] . 该反应 以芳基甲基型化合物作为起始底物, 亚硝酸叔丁酯作为 氧化剂, 可以原位产生芳基羧酸 NHPI 酯, 随后在加热 图 9 芳基羧酸衍生物的脱羧硼酯化反应 Scheme 9 Decarboxylative borylation of aryl carboxylic acid derivatives 图 10 经由芳基羧酸 NHPI 酯的 C(aryl)-CH 3 硼酯化反应 Scheme 10 Borylation of C(aryl)-CH 3 bond via N-hydroxyphthalimide ester 条件下经吡啶衍生物的活化, 实现自由基过程的硼酯化 反应.…”
Section: 芳基羧酸衍生物的脱羧-硼酯化反应unclassified
“…[5] Fortunately,aconsiderable number of remarkable transition-metal-free synthetic protocols are reported daily. [6][7][8][9][10] In recent years,o ur research group has developed efficient, accessible,e conomic,a nd environmentally friendly protocols for the functionalization of simple N-heterocycle substrates to give relevant bioactive precursors. [11] Thesuccess of this direct functionalization of pre-existing N-heterocycles lies in the highly selective CÀHo xidation at the a position mediated by cheap and environmentally friendly reagents such as NaClO 2 ,N aOCl, and 2,2,6,6-tetramethylpiperidinyloxyl (TEMPO), in which, under modulated conditions,t he C À Hoxidation at the b position can be achieved, even under catalytic conditions.…”
mentioning
confidence: 99%